Satisfacción laboral del personal de salud y su relación con la percepción de la calidad por los usuarios atendidos en una Clínica de Salud mental en Puerto Colombia - 2019 (2021)
Objective: The objective of the research was to evaluate the relationship between job satisfaction of health personnel with the perception of quality by patients of Clinical of Mental Disease in the municipality of Puerto Colombia during the period 2019. Materials and Methods: The research was quantitative, cross-sectional, descriptive-correlational. The instrument used by the Clinical was user satisfaction surveys based on Resolution 256/2014 with a 95% CI and the S21 / 26 questionnaire for collaborators with an alpha of 0.90. The Clinical provided the Microsoft Excel databases used in the investigation. The data analysis and the results of the instruments were made in the STATGRAPHICS PLUS® and R_CRAN programs. Results: higher percentage of women 62% [p = 0.000] and difference between age by sex (W: 1,2E6; p: 0.0000) both values with great significance. In age groups, greater significance was obtained in the Youth group (p: 0.0022) and Mature Adult (p: 0.0120). Regarding areas and services, they obtained positive scores above 80% satisfaction for both services. For employees, there is no statistical difference between satisfaction and areas (p> 0.05), there is no relationship between the Type of Contract and the Degree of Satisfaction, concluding both variables are independent (χ²: 2,250; p: 0.3247). The analysis of simple correspondence to the collaborators shows marked dissatisfaction in the healthcare area. Conclusions: The results obtained show that there is a direct relationship between the satisfaction of internal customers and the satisfaction of the users served.